2020
DOI: 10.1038/s41598-020-77538-5
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and ERP evidence of the self-advantage of online self-relevant information

Abstract: The present study examined whether individuals experienced the same cognitive advantage for online self-relevant information (nickname) as that experienced for information encountered in real life (real name) through two experiments at both the behavioural and neural levels (event-related potential, ERP). The results indicated that individuals showed the same cognitive advantage for nicknames and real names. At the behavioural level, a nickname was detected as quickly as the real name, and both were detected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A number of studies have shown that amplitude of the P3b component (centro-parietal P300) of the ERP increases in response to self-relevance, irrespectively to stimulus type. Such P3b effect was observed for self-faces 3 , 29 , 30 , 34 , 36 , 37 , 55 59 , as well as for visually presented own name 3 , 56 , 60 62 or online nickname 63 , autobiographical information 18 , and trait adjectives evaluation 64 , 65 . The self-related increase of the P3b has usually been interpreted as an enhancement of neural processing, presumably related to increased allocation of attention.…”
Section: Introductionmentioning
confidence: 86%
“…A number of studies have shown that amplitude of the P3b component (centro-parietal P300) of the ERP increases in response to self-relevance, irrespectively to stimulus type. Such P3b effect was observed for self-faces 3 , 29 , 30 , 34 , 36 , 37 , 55 59 , as well as for visually presented own name 3 , 56 , 60 62 or online nickname 63 , autobiographical information 18 , and trait adjectives evaluation 64 , 65 . The self-related increase of the P3b has usually been interpreted as an enhancement of neural processing, presumably related to increased allocation of attention.…”
Section: Introductionmentioning
confidence: 86%
“…The spatial resolution advantages of functional magnetic resonance and PET provide important brain regions for self-processing. Studies have shown that individuals induced specific early and late EEG components [ 14 , 15 ] in the process of self-recognition, and unique functional area activation [ 16 ] appeared in the cerebral cortex.…”
Section: Introductionmentioning
confidence: 99%